Copper Flash Smelting Process Balance Modeling - María Bacedoni; Ignacio Moreno-Ventas; Guillermo Ríos (Metals, 2020)
Process control in flash smelting is based on mass and energy balance from which the operational parameters (oxygen coefficient, oxygen enrichment, and flux demand) are obtained to achieve matte and slag with defined compositions and at defined temperatures. Mineral compositions of copper concentrates, and their blends, have been used in order to optimize the heat process balance. The classical balance methodology has been improved by using equations for molecular ratios and distribution coefficients that have been calculated using FactSage™. This paper describes the development of balance equations and compares their theoretical (equilibrium) results with industrial data logs of the smelting process.